2013
DOI: 10.4103/0971-9784.105361
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial protection during off pump coronary artery bypass surgery: A comparison of inhalational anesthesia with sevoflurane or desflurane and total intravenous anesthesia

Abstract: The study did not reveal any difference in myocardial protection after OPCAB with either sevoflurane or desflurane or TIVA using propofol as assessed by measuring serial cTnT values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…Nevertheless, most of those studies were performed in patients undergoing coronary artery bypass grafting (CABG), while few studies in non-CABG patients. Furthermore, high quality meta-analyses in adult cases have showed controversial or contradicting results [1015]. In this study, we compared the cardioprotective effect of anesthesia with intravenous propofol and inhaled sevoflurane in patients undergoing mitral, aortic or tricuspid valve replacement surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, most of those studies were performed in patients undergoing coronary artery bypass grafting (CABG), while few studies in non-CABG patients. Furthermore, high quality meta-analyses in adult cases have showed controversial or contradicting results [1015]. In this study, we compared the cardioprotective effect of anesthesia with intravenous propofol and inhaled sevoflurane in patients undergoing mitral, aortic or tricuspid valve replacement surgery.…”
Section: Introductionmentioning
confidence: 99%
“…We did not observe a significant effect of desflurane on blood concentrations of markers of myocardial ischaemia: troponin I and CK-MB. Earlier studies demonstrated conflicting results: a decreased concentration after volatile anaesthesia [12,14], or no effect [10,[15][16][17][18]. In two studies published recently, late postconditioning with sevoflurane used for sedation after coronary surgery also did not provide reduction of troponin release [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…• One trial in Japan [49], one in Korea [51]; three in India [73,76,77]; two in Taiwan [31,58]; and one trial in China [47]. • Three trials did not specify where the study was conducted [44,71,80].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Various anaesthetics agents were used in the different trials. 44 studies used propofol [ [30,42,60,62,63,70,78]; halothane in two trials [70,79]; sufentanil in three trials [37,43,62]; TIVA in six studies [26,34,40,56,73,76]; midazolam in six trials [36,37,44,52,62,70]; and, in one trial each, thiopental [60]; flunitrazepam [41]; and thiopentone and diazepam and fentanyl and droperidol and pancuronium [65].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation